An Optimized Model of Single Phase Self Excited Induction Generator - Singh, Gurdiyal; Singh, Ved Ram (Trends in Sciences, 2022)
This paper illustrates the newly developed specially designed single phase self excited induction generator. All possible configurations for winding arrangement have been attempted to obtain the best output from the model. The earlier configurations were found incomplete to obtain the optimum output from the single phase induction machine as an induction generator. The proposed model is unified, optimum and accurate for inculcating the performance of single phase induction generator. The model design as well as its development of 3.7 kW, 50 Hz and 4-pole single phase SEIG is presented using simulink in MATLAB. The 4 possible configurations are designed for single phase SEIG, the objective function is to reduce total harmonic distortion (THD) and optimize the model parameter. The results were demonstrated experimentally validated using SPEED software. A standard available IEC 132 frame size is used for development of proposed model and the results found are prominent. HIGHLIGHTS It is found that there is heavy demand for small capacity power generation in single phase rating as almost electrical appliances are operated on single phase supply. The main objective of this research is to develop a novel and a specially designed SEIG and to analyze its performance analysis The 1-phase SEIG is proposed with rating 3 - 5 kW. The input parameter for single phase SEIG such as power, voltage, impedance, frequency, pole pair the stator/rotor resistance etc are theoretically analyzed Afterwards the parameters are act as input for SPEED software the results are obtained and found to be impressive one with practical applications Four possible configurations for a single phase SEIG are proposed. The four possible configurations have been attempted to achieve the objective of research. On comparing the performance of these models, it has been observed that the model - “Short pitch (1-8) Double layer distributed winding” gives good performance in terms of reduced THD, sinusoidal m.m.f. waveforms GRAPHICAL ABSTRACT